Enhancement of immunomodulatory effect of licorice after honey-roasting based on gut microbiota and fecal metabolomics. Issue 1 (31st December 2023) - Li, Xinliang; Sun, Jie; Wu, Yixuan; Li, Cunyu; Peng, Guoping; Zheng, Yunfeng
ABSTRACT: In this study, an immunocompromised rat model was established by long-term diet control and excessive swimming and treated with extracts of raw licorice (RL) and honey-roasted licorice (HL) to explore the immunomodulatory efficacy and gut microbiota composition with their metabolites. Pharmacological experiment confirmed that honey-roasting enhanced the ability of RL to regulate inflammatory cytokines and gut mucosal-layer homeostasis. The analysis of 16S rRNA sequences showed that both RL and HL regulated the balance of gut microbiota, but HL exhibited better effects than RL in regulating microbiota closely related to inflammatory cytokines ( Coriobacteriaceae_UCG-002 ) as well as short-chain fatty acids-producing bacteria ( Dubosiella and Ruminococcus ). Moreover, HL improved the contents of butyrate and isobutyrate in feces more significantly than RL. In conclusion, the balance of gut microbiota and short-chain fatty acids might be one of the pathways that honey-roasting improve the immunomodulatory efficacy of licorice. Abbreviations: ANOVA: analysis of variance; BCA: bicinchoninic acid; ELISA: enzyme-linked immunosorbent assay; HRP: horseradish peroxidase; LDA: the linear discriminant analysis; LEfSe: the linear discriminant analysis effect size; MS: mass spectrometry; OTU: operational taxonomic units; PBS: phosphate buffered saline; PCoA: principal coordinate analysis; PVDF: polyvinylidene fluoride; RIPA: radio immunoprecipitation assay; SCFAs: short-chain fatty acids;